An Assessment of Vegetation Variables in The Reclamation Area of The Ex-Gold Mining at Ratatotok, Southeast Minahasa (Jurnal Penelitian Kehutanan Wallacea, 2018)
The reclamation area of the ex gold-mining PT. Newmont Minahasa Raya (PT. NMR) will be used as a botanic gardens. This study aims to assess the reclamation program's success based on a variable vegetation of the ex gold-mining area of PT. NMR for the basis of the next management. Observations of vegetation on each unit of area was done by nested sampling system, where plots were placed along a perpendicular transect in a contour line. Vegetation variables were recorded among other: species name, individual number, plot numbers, coordinates, temperature, humidity, canopy cover, and land cover. The effect of vegetation on both of two variable regions, revegetation area and non-revegetation area, was tested using discriminant analysis. The results showed that the vegetation composition of the ex gold mining area of PT. NMR was still dominated by introduction species i.e. gamal (Gliricidia sepium), mahoni (Swietenia macrophylla), and lamtoro (Leucaena leucocephala). The diversity of understorey vegetation was middle category. The vegetation structure of the revegetation area was still in its infancy and has not yet reached climax conditions. However, revegetation efforts PT. NMR has succeeded in restoring the composition and structure of vegetation resembling to vegetation conditions in secondary forests. For supporting the ecosystem stability and promoting development programs of botanic gardens, were the enrichment of native vegetation and endangered species is needed.
Keywords: Vegetation analysis; Reclamation; Gold mining